2021
DOI: 10.1200/jco.21.00006
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy Versus Inguinofemoral Lymphadenectomy as Treatment for Vulvar Cancer Patients With Micrometastases in the Sentinel Node: Results of GROINSS-V II

Abstract: PURPOSE The Groningen International Study on Sentinel nodes in Vulvar cancer (GROINSS-V)-II investigated whether inguinofemoral radiotherapy is a safe alternative to inguinofemoral lymphadenectomy (IFL) in vulvar cancer patients with a metastatic sentinel node (SN). METHODS GROINSS-V-II was a prospective multicenter phase-II single-arm treatment trial, including patients with early-stage vulvar cancer (diameter < 4 cm) without signs of lymph node involvement at imaging, who had primary surgical treatment (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 11 publications
0
83
1
Order By: Relevance
“…Six isolated groin recurrences occurred (3.8% at 2 years). The 18 patients who did not receive any further treatment had a significantly higher ipsilateral isolated groin recurrence rate than those who were treated with radiotherapy according to protocol (2 year 11.8% vs 1.6%, p=0.006) 42. Overall, GROINSS-V II showed that inguinofemoral radiotherapy with 50 Gy is a safe alternative to inguinofemoral lymphadenectomy in patients with sentinel node metastasis ≤2 mm, but not for patients with sentinel node metastasis >2 mm 42.…”
Section: Risk Factors For Nodal Recurrence and Radiotherapy Indicationsmentioning
confidence: 91%
See 3 more Smart Citations
“…Six isolated groin recurrences occurred (3.8% at 2 years). The 18 patients who did not receive any further treatment had a significantly higher ipsilateral isolated groin recurrence rate than those who were treated with radiotherapy according to protocol (2 year 11.8% vs 1.6%, p=0.006) 42. Overall, GROINSS-V II showed that inguinofemoral radiotherapy with 50 Gy is a safe alternative to inguinofemoral lymphadenectomy in patients with sentinel node metastasis ≤2 mm, but not for patients with sentinel node metastasis >2 mm 42.…”
Section: Risk Factors For Nodal Recurrence and Radiotherapy Indicationsmentioning
confidence: 91%
“…For nodal bed, the suggested dose is 50–55 Gy if pathologically node positive with no extranodal extension or gross residual disease, 54–64 Gy if extranodal extension, and 60–67 Gy for gross residual nodal disease 47. Beyond investigating the addition of concurrent chemotherapy, the ongoing GROINSS-V III study is also evaluating the role of increasing the total dose in the involved groin from 50 to 56 Gy by applying a boost 42…”
Section: Radiotherapy Planning and Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings have led to the practice of omitting regional lymph node dissection in vulvar cancer when SLNs are negative. Recently, the GROINSS-V II prospective cohort study evaluated whether the use of inguinofemoral radiotherapy (50 Gy) could replace complete inguinofemoral lymph node dissection in patients with vulvar cancer (<4 cm) who have a positive SLN [ 18 ]. Due to a high rate of groin recurrence in patients with macrometastases (>2 mm), the protocol was amended to include complete inguinofemoral lymph node dissection in those with macrometastases only.…”
Section: Introductionmentioning
confidence: 99%